Intrathermocline eddies observed in the northwestern subtropical Pacific Ocean - Cai, Shangzhan; Huang, Jiang; Wang, Weibo; Jing, Chunsheng; Xu, Jindian; Li, Kai; Kuang, Fangfang (Frontiers in Marine Science, 2024)
Two anticyclonic intrathermocline eddies (ITEs) were detected by an underwater glider in the northwestern subtropical Pacific Ocean during August-October 2019. They both exhibited a lens-shaped vertical structure within the thermocline with their cores located at 170 m. The North Pacific Subtropical Mode Water (STMW) was found within the cores of these two ITEs. The lens-shaped structure of ITE1 observed by the glider was very clear since the glider seemed to have moved into its core during the observation. Further analysis reveals that ITE1 displayed no signals at the sea surface and lasted for about 20 days (26 August-14 September 2019). ITE1 was locally formed and the water inside it was a mixture of local water and the water in the northern adjacent area. The low-salinity water at 0-50 m from the northern adjacent area extended southwestward and mixed with the local water. As a result, the local salinity-forced restratification caused a potential vorticity (PV) decrease in the subsurface and finally resulted in the generation of ITE1. The baroclinic instability at 50-170 m may be the main energy source for ITE1 generation. On the other hand, the lens-shaped structure of ITE2 observed by the glider was less prominent since the glider did not move into its core. Further analysis reveals that the lens-shaped structure of ITE2 was also very clear near its core and ITE2 displayed clear signals at the surface as an anticyclonic eddy (AE2). AE2/ITE2 was remotely generated within the main formation region of STMW and then moved southwestward. The low PV STMW was trapped in AE2 and a lens-shaped structure developed in the subsurface. Subduction of the STMW caused the generation of ITE2.